Draft Annual Plan 2011-2012 Volume-II - Planning Commission (Planning Commission, 2011)
Sikkim has entrusted the Department of Commerce to ""Industrialize Sikkim"" and make the State self-reliant and self-sufficient. Accordingly, the Department has formulated various policies on subsidies and facilities for the benefit of investors in Sikkim. The Department has been able to woo various industrialists and investors ranging from food processing units to pharmaceutical Units. This has solved some unemployment problem in the State and has been able to create indirect revenue for the State Exchequer. Further, special incentives for Women entrepreneurs have been provided by the State Government as a part of Women empowerment under Sikkim Industrial Promotion and Incentive Act.
Development Planning, Economic Reforms & North Eastern Council Affairs Department Government of Sikkim